WEB Based Motorcycle Sales Information System - Ayu Andini (Information Technology Studies Journal (ITECH), 2024)
Motorcycles sold by PT. So Kencana Motor is provided with market needs so that sales have a lot of profits and supplies do not accumulate in the warehouse. Each sales transaction is processed using the Microsoft excel application. The problem that occurs is that when doing data search and report printing, then the administration must look for it one by one from excel data that has been stored a lot. So this complicates the administration in managing motorcycle sales. This research makes information systems created using web programming that implement systems based on sales reports into applications that can managemotorcycle sales until the printing of reports. With the existence of a web-based motorcycle sales information system, PT. Source So Kencana Motor gets convenience in managing sales data until the printing of reports..